Data Analysis and Visualization Training on Microsoft Excel Using Artificial Intelligence At SMA N 1 Ampek Angkek Kabupaten Agam - Tessy Octavia Mukhti; Fadhilah Fitri; Devni Prima Sari (Fakultas MIPA Universitas Negeri Padang, 2023)
Based on observations and discussions with several teachers at SMA N 1 Ampek Angkek Kabupaten Agam, problems were found in describing and analyzing the significance of the development of students' abilities. The next problem which is no less important is the difficulty of measuring the effectiveness of the teaching materials used in the classroom. To improve the quality of learning, teachers are required to optimize the learning process by making students actively involved and making learning more interesting for them. To overcome this problem, data analysis and visualization training was carried out in Microsoft Excel using artificial intelligence at SMA N 1 Ampek Angkek Kabupaten Agam.